New species and combinations in the genus Protoparmeliopsis (Lecanoraceae, Lichenized Ascomycota) - Kondratyuk, S.Y.; Zarei-Darki, B.; Khajeddin, S.J. (Український ботанічний журнал, 2012)
Two new species of the genus Protoparmeliopsis M. Choisy, P. zareii S.Y. Kondr. and P. esfahanensis S.Y. Kondr. & B. Zarei-Darki, are described, compared with closely related taxa, and illustrated. Twenty thee new combinations for the following taxa are proposed: Protoparmeliopsis baicalensis (for Lecanora baicalensis Zahlbr.), P. ba ranowii (for Lecanora baranowii Tomin), P. bipruinosum (for Le canora bipruinosa Fink), P. bog do e n sis (for Lecanora bogdoensis Tomin), P. chlorophtha l mum (for Lecanora chlorophthalma Poelt & Tomin), P. crustaceum (for Squamarina crustacea Savicz), P. degelii (for Squamarina degelii Poelt), P. dispersoareolatum (for Placodium dispersoareolatum Körb.), P. geisereae (for Le canora geisereae B.D. Ryan), P. hieroglyphicum (for Le ca nora hieroglyphica Poelt), P. kofae (for Lecanora kofae B.D. Ryan & T.H. Nash), P. kotovii (for Placodium kotovii Oxner), P. kukunorensis (for Lecanora kukunorensis H. Magn.), P. mazatzalensis (for Lecanora mazatzalensis B.D. Ryan & T.H. Nash), P. nashii (for Lecanora nashii B.D. Ryan), P. novomexicanum (for Lecanora no vo mexi cana H. Magn.), P. orbicularis (for Lecanora po ly t ropa var. orbicularis Schaer.), P. phaedrophthalmum (for Lecanora phaedrophthalma Poelt), P. sierrae (for Lecanora sierrae B.D. Ryan & T.H. Nash), P. sphaeroideum (for Pla codium sphaeroideum Oxner), P. stramineum (for Par melia straminea Wahlenb.), P. uzbekicum (for Le canora uzbekica Poelt) and P. verruculiferum (for Placodium verruculiferum Oxner). Наведено описи, порівняння з близькоспорідненими видами двох нових для науки видів роду Protoparmeiopsis M. Choisy — P. Zareii S.Y. Kondr. і P. esfahanensis S.Y. Kondr. & B. Zarei-Darki. Крім того, запропоновані нові комбінації назв 23 лишайників, у тому числі: Pro to par meliopsis baicalensis, P. baranowii, P. bipruinosum, P. bogdoensis, P. chlorophthalmum, P. crustaceum.